Hybrids of SiO2 substrate and electrospun Ni-MOF/polysulfone fibers for an efficient removal of CH4 gas pollution - Geesi, Mohammed H.; Jalil, Abduladheem Turki; Riadi, Yassine; Aljohani, Talal A.; Alameri, Ameer A. (Frontiers in Materials, 2023)
In this study, novel nanostructures based on Ni-MOF/polysulfone (Ps) nanofibers were fabricated by microwave-assisted electrospinning method. The final Ni-MOF/ polysulfone fibrous nanostructure were immobilized on SiO2 substrates with high physicho-chemical properties. These nanostructures with an average diameter of 20 nm and a specific surface area of 1690 m2/g were used as novel adsorption for CH4 gas adsorption. It seems that the integration of novel Ni-MOF compounds into the fibrous network has differentiated these materials from previous samples. Since the experimental parameters significantly affect the specific surface area, the parameters including voltage, concentration, and distance between the collector and source are designed by the fractional factorial method. The results were optimized by contour plots, ANOVA and surface plots, theoretically. The results show that the sample has an adsorption rate of about 5.14 mmoL/g. The improved CH4 gas adsorption performance is attributed to the large specific surface area and porous nature of the Ni-MOF/Ps nanostructure which is more convenient and accessible for CH4 gas adsorption.